2015
DOI: 10.5966/sctm.2014-0111
|View full text |Cite
|
Sign up to set email alerts
|

The Secretome of Hydrogel-Coembedded Endothelial Progenitor Cells and Mesenchymal Stem Cells Instructs Macrophage Polarization in Endotoxemia

Abstract: We previously reported the delivery of endothelial progenitor cells (EPCs) embedded in hyaluronic acid-based (HA)-hydrogels protects renal function during acute kidney injury (AKI) and promotes angiogenesis. We attempted to further ameliorate renal dysfunction by coembedding EPCs with renal mesenchymal stem cells (MSCs), while examining their paracrine influence on cytokine/chemokine release and proinflammatory macrophages. A live/dead assay determined whether EPC-MSC coculturing improved viability during lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 53 publications
1
46
0
Order By: Relevance
“…Our own observations (10) supplement this data with findings obtained in septic mice receiving a combination therapy with mesenchymal stem and endothelial progenitor cells, each acting via the secretome to elicit beneficial effect. The cyto-/chemokine release from embedded stem cells was examined including effects on modulating the polarization and release of proinflammatory molecules from macrophages (Fig.…”
Section: Sepsis and Effects Of Bone Marrow Stromal Cells On Macrophagessupporting
confidence: 72%
See 1 more Smart Citation
“…Our own observations (10) supplement this data with findings obtained in septic mice receiving a combination therapy with mesenchymal stem and endothelial progenitor cells, each acting via the secretome to elicit beneficial effect. The cyto-/chemokine release from embedded stem cells was examined including effects on modulating the polarization and release of proinflammatory molecules from macrophages (Fig.…”
Section: Sepsis and Effects Of Bone Marrow Stromal Cells On Macrophagessupporting
confidence: 72%
“…Exposure of proinflammatory M1 macrophages to EPC-MSC conditioned culture medium changed their polarization to anti-inflammatory M2 macrophages, while EPC-MSC delivery to endotoxemic mice elevated levels of circulating M2 macrophages. Incubation of co-embedded EPC-MSC with macrophages altered their release of cyto-/chemokines including enhanced release of anti-inflammatory IL-10 from macrophages (10). …”
Section: Sepsis and Effects Of Bone Marrow Stromal Cells On Macrophagesmentioning
confidence: 99%
“…Various soluble factors secreted by MSCs, including IL-4 [50], IL-13 [51], prostaglandin E2 (PGE2) [52], and tumor necrosis factor-α-induced gene/protein 6 (TSG-6) [53], have been shown to play a critical role in modulating inflammatory processes and macrophage polarization towards the M2 phenotype in animal models of sepsis [54], acute kidney injury [17], experimental colitis [18], spinal cord injury [19], and skin wounds [1]. To determine the key factors responsible for macrophage polarization towards the M2 phenotype induced by DFSC-CM, we performed a protein array, which revealed that rDFSCs could release many secreted proteins, including immunomodulatory factors, growth factors, cytokines, chemokines and neurotrophic factors, thus providing useful information for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MSCs have been shown to regulate immune responses by suppressing the proliferation and activation of T and B cells, and promote the generation of regulatory T cells, manifesting the immunosuppressive functions [13,14]. In addition, MSCs elicit a phenotypic switch from M1 to M2 macrophages in vitro [15,16] as well as in animal models of acute kidney injury [17], experimental colitis [18], spinal cord injury [19], and skin wounds [1]. MSCs affect neighboring immune cells primarily through direct cell-to-cell contact and/or various soluble factors [12][13][14]20].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the cell-toMPs' cooperation is depended on presentation of the surface of the vesicles and target cells appropriate recognizing antigens, which interact with secreted proteins and consequently regulate in different manner the tissue response via switching specific transmembrane signal systems to nuclear transcriptional factors (i.e., NK-kB). Recently it has been shown that the components of the secretome might be attributes of overactive immune system during antigen stimulation and probably act to counterbalance the release of many inflammatory and damageable substances, thereby improving the associated vascular injury and tissue damages [23].…”
Section: Secretome and Its Componentsmentioning
confidence: 99%